Formulasi Polluter Pays Principle dalam Rangka Mengurangi Permasalahan Sampah Plastik di Daerah Istimewa Yogyakarta - Rama Hendra Triadmaja; M. David Hanief (Fakultas Hukum Universitas Islam Indonesia, 2024)
The problem of plastic garbage is one of the environmental issues that is very difficult to solve, including in Yogyakarta Special District. It seems that the massive use of plastic by various parties is the main cause of the environmental problems. Therefore, there is a need for an instrument to prevent continued pollution, the Polluter Pays Principle. Implementation of the Polluter Pays Principle is expected to be able to reduce the issue of garbage and raise public awareness about reducing the use of plastic waste. This research aims to provide advice that can be used to reduce the issue of its original origin, i.e. the massive production and consumption of plastic garbage. This type of research is normative jurisprudence that is descriptive analytically using a statute approach, a conceptual approach, and a comparative approach. (comparative approach). The results of this study suggest that the Polluter Pays Principle needs to be formulated in order to reduce the overload of garbage that causes environmental pollution in Yogyakarta Special District. The Yogyakarta Special Territory Government can formulate the Polluter Pays Principle in the Regional Regulations as a legal instrument that can contain criminal sanctions for the parties who violate. The practice of implementing the Polluter Pays Principle has proven to be successful in reducing the dump in some countries can be a matter of consideration in the formulation of this principle.